Comparison between open and pharmacomechanical repair of acutely thrombosed arteriovenous hemodialysis fistulae within a decade - Regus, Susanne; Almási-Sperling, Veronika; Rother, Ulrich; Meyer, Alexander; Schmid, Axel; Uder, Michael; Lang, Werner (Hemodialysis International, 2018)
INTRODUCTION: Different declotting techniques are available for acutely thrombosed arteriovenous hemodialysis fistulae (AVF). The aim of this single-center study was to compare immediate and follow-up results between surgical repair and a modified interventional lyse-and-wait technique characterized by prolonged local reaction times of recombinant tissue-plasminogen activator (rtPA). MATERIALS AND METHODS: We retrospectively analyzed medical records of 110 consecutively treated patients between the years 2003 and 2013. All patients were on hemodialysis (HD) and suffered from an acutely thrombosed AVF. The treatment standards changed in the course of time, wherefore we compared 2 groups: the open repair (OR) (N = 50) and the endovascular repair (ER) group (N = 60). FINDINGS: We found no significant differences in success rates (OR 92%/ER 96.7%; P = 0.28), immediate failures (IFs) (OR 8%/ER 10%; P = 0.71), and temporary catheter placements (TCPs) (OR 10%/ER 6.7%; P = 0.52). Furthermore, there were no differences in cumulative primary patency rates (P = 0.42) and secondary patency rates (P = 0.97).The infection rate was significantly increased after OR (8%) compared to ER (0%); P = 0.026. The hospital stay in days was shorter after ER (5.2 ±2.8) vs. OR (9.0 ± 3.5); P < 0.001. CONCLUSION: The modified lyse-and-wait technique with prolonged local reaction times is a successful alternative to surgical repair for acutely thrombosed AVF. Clear benefits are less infections and significant shorter hospital stays after ER. However, OR remains the preferred treatment for aneurysms and anastomotic stenoses.
EVALuna2:36234

Cracking the perfusion code?: Laser-assisted Indocyanine Green angiography and combined laser Doppler spectrophotometry for intraoperative evaluation of tissue perfusion in autologous breast reconstruction with DIEP or ms-TRAM flaps - Ludolph, Ingo; Arkudas, Andreas; Schmitz, Marweh; Boos, Anja; Taeger, Christian; Rother, Ulrich; Horch, Raymund E.; Beier, Justus (Journal of Plastic Reconstructive and Aesthetic Surgery, 2016)
The aim of this prospective study was to assess the correlation of flap perfusion analysis based on laser-assisted Indocyanine Green (ICG) angiography with combined laser Doppler spectrophotometry in autologous breast reconstruction using free DIEP/ms-TRAM flaps. Between February 2014 and July 2015, 35 free DIEP/ms-TRAM flaps were included in this study. Besides the clinical evaluation of flaps, intraoperative perfusion dynamics were assessed by means of laser-assisted ICG angiography and post-capillary oxygen saturation and relative haemoglobin content (rHb) using combined laser Doppler spectrophotometry. Correlation of the aforementioned parameters was analysed, as well as the impact on flap design and postoperative complications. Flap survival rate was 100%. There were no partial flap losses. In three cases, flap design was based on the angiography, contrary to clinical evaluation and spectrophotometry. The final decision on the inclusion of flap areas was based on the angiographic perfusion pattern. Angiography and spectrophotometry showed a correlation in most of the cases regarding tissue perfusion, post-capillary oxygen saturation and relative haemoglobin content. Laser-assisted ICG angiography is a useful tool for intraoperative evaluation of flap perfusion in autologous breast reconstruction with DIEP/ms-TRAM flaps, especially in decision making in cases where flap perfusion is not clearly assessable by clinical signs and exact determination of well-perfused flap margins is difficult to obtain. It provides an objective real-time analysis of flap perfusion, with high sensitivity for the detection of poorly perfused flap areas. Concerning the topographical mapping of well-perfused flap areas, laser-assisted angiography is superior to combined laser Doppler spectrophotometry.
EVALuna2:15280

Dosing of indocyanine-green for intraoperative laser fluorescence angiography in kidney transplantation - Rother, Ulrich; Gerken, Andreas L. H.; Karampinis, Ioannis; Klumpp, Madeline; Regus, Susanne; Meyer, Alexander; Apel, Hendrik; Kraemer, Bernhard K.; Hilgers, Karl Friedrich; Lang, Werner; Nowak, Kai (Microcirculation, 2017)
Sufficient blood supply is a crucial factor determining postoperative allograft function in kidney transplantation. Therefore, besides the surgeon's individual impression a method for evaluating the quality of the organ's microperfusion is required. Laser fluorescence angiography with indocyanine-green (ICG) is an emerging tool for this purpose. However, no reproducible quantification of ICG fluorescence has been performed in transplantation so far.This retrospective two-center study was designed to evaluate the dosing of ICG for intraoperative laser fluorescence angiography in kidney transplantation. The Spy Elite(®) system (NOVADAQ, Canada) was employed for quantitative assessment of allograft microperfusion. ICG was administered systemically 5 min after reperfusion applying doses between 0.25 and 0.01 mg ICG per kg body weight. Quantitative assessment was performed with the implemented SPY-Q Software.57 kidney recipients were included in two centers. The generated curves showing ICG ingress and egress rates were not evaluable due to oversensing when doses exceeded 0.02 mg per kg body weight.Fluorescence angiography with ICG is an emerging tool for the intraoperative quality control and evaluation of microperfusion in kidney transplantation. A dose of 0.02 mg ICG per kg body weight is recommended in order to ensure the quantitative assessment with SPY-Q. This article is protected by copyright. All rights reserved.
EVALuna2:3964

Eligibility of Endovascular Repair for Popliteal Artery Aneurysms According the Instructions for Use - Hellwig, Konstantin; Hoffmann, Lisa; Rother, Ulrich; Meyer, Alexander; Lang, Werner; Schmid, Axel (Annals of Vascular Surgery, 2020)
Background: Popliteal artery aneurysms (PAAs) are the most common peripheral aneurysms. Although rare and often asymptomatic, there is a significant risk of thrombosis, embolism, and limb loss. The aim of this study was to evaluate the eligibility for endovascular repair of patients treated for symptomatic and asymptomatic PAAs in accordance with the instructions for use (IFU). Methods: All patients treated for PAA with open surgical repair between the years 2010 and 2017 were analyzed if suitable for endovascular treatment. Preoperative imaging was reviewed for applicability with an interventional radiologist and 2 vascular surgeons. Evaluation was performed in accordance with the following criteria adopted from the IFU of the Gore ® Viabahn stent graft: at least a single-vessel tibial runoff, proximal and distal landing zone more than 2 cm, no large difference in vessel diameter proximal and distal to the aneurysm, no overstenting of significant collaterals necessary, and no inadequate kinking of the artery. The patients were classified in 3 categories: the patient was eligible, endovascular treatment was feasible, and endovascular treatment was not appropriate. Results: 51 patients with 61 symptomatic and asymptomatic PAAs were identified. Forty-five cases were asymptomatic, 11 cases showed clinical symptoms such as claudication, and in 5 cases, the patients presented with acute ischemia. Twenty-four patients were eligible for endovascular intervention, 14 cases were feasible, and in 23 cases, it was not appropriate in accordance with the IFU. Conclusions: In this study, more than one-third of the patients with PAA were not eligible for endovascular treatment in accordance with the IFU and another 23 % showed substantial reasons against endovascular treatment. These data suggest that endovascular repair remains a treatment option for selected patients only. Cross-sectional imaging is mandatory for procedure selection.
CRIS-Team Scopus Importer:2020-05-12

Immediate changes of angiosome perfusion during tibial angioplasty - Rother, Ulrich; Krenz, Katrin; Lang, Werner; Horch, Raymund E.; Schmid, Axel; Heinz, Marco; Meyer, Alexander; Regus, Susanne (Journal of Vascular Surgery, 2017)
In recent years, a controversial discussion about the clinical relevance of the angiosome concept during tibial angioplasty has developed. Therefore, we conducted a prospective study to evaluate the angiosome concept on the level of microcirculation during tibial vascular interventions.Thirty patients with isolated tibial angioplasty were examined prospectively. Macrocirculation was evaluated by measurement of the ankle-brachial index (ABI). For the assessment of microcirculation, a combined method of laser Doppler flowmetry and tissue spectrometry (O2C; LEA Medizintechnik GmbH, Giessen, Germany) was applied. Microcirculatory parameters were measured continuously during the procedures. Measuring points were located over different angiosomes of the index foot; a control probe was placed on the contralateral leg.Cumulated microcirculation parameters (sO2, flow) as well as the ABI showed a significant improvement postinterventionally (ABI, P < .001; sO2, P < .001; flow, P < .001). Assessment of the separate angiosomes of the index leg and the comparison of the directly revascularized (DR) and indirectly revascularized (IR) angiosomes showed no significant difference concerning the microperfusion postinterventionally (DR - IR: sO2, P = .399; flow, P = .909) as well as during angioplasty. Even a further subdivision of the collective into patients with diabetes (sO2, P = .445; flow, P =.758) and renal insufficiency (sO2, P = .246; flow, P = .691) could not demonstrate a superiority of the direct revascularization at the level of microcirculation in these patients (comparison DR - IR).There is a significant overall improvement in tissue perfusion of the foot immediately after tibial angioplasty. The effect shown in this study, however, was found to be global and was not restricted to certain borders, such as defined by angiosomes.
EVALuna2:14616

Indocyanine green angiography and the old question of vascular autonomy - Long term changes of microcirculation in microsurgically transplanted free flaps - Ludolph, Ingo; Arkudas, Andreas; Lang, Werner; Rother, Ulrich; Horch, Raymund E.; Cai, Aijia (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Free tissue transfer has become a routine procedure with low failure. In case of a compromised vascular pedicle, flap survival is time dependantly possible due to flap autonomization. However it remains unknown at what time and to which degree different factors influence flap autonomization.
CRIS-Team WoS Importer:2019-10-15

INDOCYANINE-GREEN FOR INTRAOPERATIVE LASER FLUORESCENCE ANGIOGRAPHY IN KIDNEY TRANSPLANTATION: PRELIMINARY EXPERIENCE AND DOSE FINDING - Rother, Ulrich; Gerken, A.; Lang, Werner; Nowak, K. (2016)
EVALuna2:15277

Major vascular complications after transfemoral arterial closure system implantation: a single-center study - Chatzigeorgiadis, Pavlos; Hellwig, Konstantin; Almási-Sperling, Veronika; Meyer, Alexander; Lang, Werner; Rother, Ulrich (International Angiology, 2020)
BACKGROUND: During the past decades, the use of vascular closure devices (VCDs) has been established due to the increasing number of interventions. Of particular concern is the perceived risk of VCDs for development of implant-induced vascular major complications. Therefore, the aim of this analysis was to report the variety of vascular access side complications after the use of VCDs, and to analyze the referred risk factors. METHODS: All cases of vascular complications associated with VCD use requiring surgical repair from 2010 to 2016 were retrospectively analyzed in a single center trial. Systemic and local complications, risk factors as pre-existing diseases and their influence on the surgical outcome were evaluated. RESULTS: A total of 46 individuals were included in this study (male/female: 16/30). The total number of interventions in the involved departments of the study center during the same period was 9754 Therefore the complication rate after VCD implantation was 0.47%. The detected complications ranged from symptomatic claudication (N.=24) to acute leg ischemia (N.=19) and major bleeding (N.=3). Surgical reconstruction was performed by direct suture (N.=4), transverse arteriotomy with thrombectomy (N.=2), endarterectomy with patchplasty (N.=35), inguinal graft interposition or bypass (N.=3) and primary major amputation (N.=2). In regard to the risk factors, the study has concluded that atherosclerosis, female gender and diabetes mellitus are correlated with major vascular complications (bleeding and limb ischemia). However, in cases with therapeutic anticoagulation the rate of major bleeding was significantly elevated (P=0.028). CONCLUSIONS: Reported complication rates associated with femoral VCD implantation are low. However, in some cases VCD implantation may account for severe complications including limb losses. Therefore, an adequate patient selection is necessary to detect those cases at higher risk for complications.
CRIS-Team Scopus Importer:2020-04-14

Microcirculation Evaluated by Intraoperative Fluorescence Angiography after Tibial Bypass Surgery - Rother, Ulrich; Lang, Werner; Horch, Raymund E.; Ludolph, Ingo; Meyer, Alexander; Regus, Susanne (Annals of Vascular Surgery, 2017)
Intact microperfusion of the foot in the critical ischemic limb remains a crucial condition for ulcer healing. Aim of this clinical study was to evaluate the immediate effect of tibial bypass surgery on the microcirculation by usage of fluorescence angiography.Prospective analysis of 33 patients presenting with critical limb ischemia (Rutherford IV-VI) undergoing tibial bypass surgery was performed. Macroperfusion was investigated by measurement of ankle-brachial index. For assessment of microperfusion, intraoperative fluorescence angiography (SPY Elite, NOVADAQ) was undertaken during general anesthesia immediately before and after operation. For each investigation, a fluorescence dye (Indocyanine green) with an amount of 0.1 mg/kg was administered intravenously. Follow-up investigations were performed to assess the clinical outcome.The mean follow-up time was 8.28 (±4.46) months. The parameters Ingress (IN) and Ingress rate (InR) of the fluorescence dye representing the microcirculation showed a significant improvement to preoperative values and correlated with the ankle-brachial index significantly. Furthermore, a significant difference between the individual improvement of the microcirculation parameters (preoperative-postoperative) between patients with postoperative clinical improvement (wound healing, absence of rest pain) and those without could be demonstrated (InR: P = 0.039, IN: P = 0.036).The parameters IN and InR significantly reproduced the postoperative improvement of the microcirculation. An increased ankle-brachial index significantly correlated with increased microcirculation parameters. A better clinical outcome was found in those patients who had a higher relative improvement of microcirculation postoperatively.
EVALuna2:15278

Outcomes and Influence of the Pedal Arch in Below-the-Knee Angioplasty in Patients with End-Stage Renal Disease and Critical Limb Ischemia - Meyer, Alexander; Schinz, Katharina; Lang, Werner; Schmid, Andrea; Regus, Susanne; Rother, Ulrich (Annals of Vascular Surgery, 2016)
Management of dialysis patients with critical limb ischemia (CLI) still represents a challenge to vascular medicine, whereas the effects of the pedal arch quality in these patients with predominant affection of the infrapopliteal vessels have rarely been evaluated. Therefore, our aim was to analyze the outcomes of infrapopliteal angioplasty in the setting of chronic renal failure (end-stage renal disease) and evaluate the influence of the pedal arch involvement on clinical success.Prospective follow-up of 32 ERSD patients on hemodialysis (mean age, 72 years) with CLI and consecutive infrapopliteal angioplasty over a 5-year period 2010-2014 was performed. Mean follow-up was 10 months (range, 0-51 months). Statistical end points were defined for amputation-free survival, overall survival, and wound healing. Each patient's pedal arch was classified in 4 categories according to patency on completion angiography and the influence of the pedal arch quality on end points was assessed.A total of 44 vessels in 32 ischemic legs were treated. Technical success was achieved in 96% of patients, no major complications were observed. A 30-day mortality rate amounted 6% with no procedure-related deaths. The 1-year amputation-free survival rate was 56% and 34% at 2 years. Two major amputations were required. Subsequent revascularization procedures were necessary in 11 patients (10 redo angioplasty, 1 pedal bypass graft). The pedal arch was classified as category I in 1 patient (3%), category IIa in 12 (38%), IIb in 3 (9%), and III in 16 patients (50%). No statistical significant differences in terms of survival or wound-healing rate were observed between those groups, and the pedal arch quality had no impact on predefined end points.End-stage renal disease patients represent a subgroup with poor prognosis of limb salvage in CLI. Amputation-free survival remains poor and based on these data, an endovascular therapy is feasible and safe in these highly multimorbid patients. The quality of the pedal arch was not found to have any impact on wound healing or survival in the present study.
EVALuna2:14613

Pilot Assessment of the Angiosome Concept by Intra-operative Fluorescence Angiography After Tibial Bypass Surgery - Rother, Ulrich; Lang, Werner; Horch, Raymund E.; Ludolph, Ingo; Meyer, Alexander; Gefeller, Olaf; Regus, Susanne (European Journal of Vascular and Endovascular Surgery, 2018)
OBJECTIVES: The "angiosome" concept as a model for decision making in revascularisation of patients with critical limb ischaemia (CLI) has been subject to lively discussion in recent years. The aim of this prospective pilot study was to use intra-operative fluorescence angiography to provide further data on the angiosome concept on the level of microcirculation after tibial bypass surgery. DESIGN, MATERIALS, AND METHODS: This was a prospective analysis of 40 patients presenting with CLI Rutherford stage IV to VI before and after tibial bypass surgery. The macrocirculation was measured by the ankle brachial index. Skin microcirculation was assessed by intra-operative fluorescence angiography. The alteration of microcirculation was compared in direct and indirect revascularised angiosomes. Clinical follow-up investigations were performed and the wound healing rate was compared between the different revascularisation methods. RESULTS: Cumulated microcirculation parameters showed a significant improvement after surgery (ingress, ingress rate p<.001). Likewise, general microcirculatory improvement was observed in each foot angiosome after revascularisation, regardless of the tibial artery revascularised. Furthermore, a comparison of the direct (DR) and the indirect revascularised (IR) angiosomes did not show a significant difference concerning the improvement of microcirculation (difference DR-IR, ingress: 1.69, 95% CI 71.73-75.11; ingress rate: 0.08, 95% CI -12.91 to 13.07). The wound healing rate was similar in both groups, although the time to wound healing was faster by on average 2.5 months in the DR group (p=.083). CONCLUSION: Microcirculatory improvement was seen over the whole foot after tibial bypass. Therefore, fluorescence angiography is a promising tool to evaluate the angiosome concept in future larger studies. Clinicaltrials.gov: NCT03012750.
EVALuna2:35687

Pilot study using intraoperative fluorescence angiography during arteriovenous hemodialysis access surgery - Regus, Susanne; Klingler, Felix; Lang, Werner; Meyer, Alexander; Almási-Sperling, Veronika; May, Matthias; Wüst, Wolfgang; Rother, Ulrich (Journal of Vascular Access, 2019)
Introduction: In this pilot study, we used indocyanine green fluorescence angiography during hemodialysis access surgery. The aim was to evaluate its relevance as a diagnostic tool to visualize changes in hand microperfusion. Patients and methods: In this prospective single-center study, 47 adult patients (33 male, 14 female) with renal disease (24 preemptive, 23 endstage) were enrolled. Surgical creation of an arteriovenous fistula was performed (22 forearm, 25 upper arm). Microperfusion of the ipsilateral hand and fingers was evaluated intraoperatively using indocyanine green fluorescence angiography. We compared the cumulated microperfusion parameters ingress (In) and ingress rate (InR) before and after opening of the anastomosis. To compare the dimension of microcirculatory decline, we calculated the ratios of the parameters (RatioIn and RatioInR) after to those before anastomosis opening. Results: The cumulated microperfusion parameters In and InR showed a significant decrease after completion of anastomosis and declamping. This effect has been seen in all patients for the hand and for each finger consecutively. During follow-up (mean 4.6, range 3-11 months), 5 patients (10.6%) complained about hemodialysis access-induced distal ischemia. The ratio of intraoperative microperfusion in those five hemodialysis access-induced ischemia patients was significantly lower compared to asymptomatic patients (RatioIn 0.23 vs 0.58, p = 0.001, and RatioInR 0.25 vs 0.62, p = 0.003). Conclusion: Intraoperative fluorescence angiography could visualize the deterioration of ipsilateral hand microperfusion after surgical creation of an arteriovenous fistula. It seems to be a promising tool to detect patients at risk for hemodialysis access-induced distal ischemia early in the peri- or even intraoperative stage.
CRIS-Team WoS Importer:2019-03-06

Quantitative assessment of microperfusion by indocyanine green angiography in kidney transplantation resembles chronic morphological changes in kidney specimens - Rother, Ulrich; Amann, Kerstin Ute; Adler, Werner; Nawroth, Nina; Karampinis, Ioannis; Keese, Michael; Manap, Serhat; Regus, Susanne; Meyer, Alexander; Porubsky, Stefan; Hilgers, Karl Friedrich; Krämer, Bernhard K.; et al. (Microcirculation, 2019)
OBJECTIVE: Indocyanine green fluorescence angiography enables a quantitative real-time perfusion assessment in kidney transplantation. The results of intraoperative microperfusion of the kidney allograft were compared to the renal chronicity score in pre-transplantation kidney biopsy specimens. The intrarenal resistance index was calculated by duplex sonography as a method of reference. METHODS: Seventy-seven patients with end stage renal disease undergoing kidney transplantation were prospectively included in two centers. Correlation analysis of chronic changes in kidney biopsy specimens and the ingress of ICG fluorescence signal were investigated. RESULTS: The results yielded a significantly negative correlation for the renal chronicity (r= -0.294, p=0.017) as well as the intestinal fibrosis and tubular atrophy score (r=-0.328, p=0.007). There was a significant inverse relationship between the ingress and the mean RI values of the upper pole of the kidney allograft. CONCLUSION: In summary, fluorescence angiography reflects preexisting morphological changes of the renal cortex. ICG angiography may serve as an alternative method for the assessment of microperfusion of the kidney allograft. This article is protected by copyright. All rights reserved.
EVALuna2:35427

Surgeon experience affects outcome of forearm arteriovenous fistulae more than outcomes of upper-arm fistulae - Regus, Susanne; Almási-Sperling, Veronika; Rother, Ulrich; Meyer, Alexander; Lang, Werner (Journal of Vascular Access, 2017)
There is still an ongoing discussion about the influence of vascular surgeon experience on the immediate and long-term outcome of newly created arteriovenous fistula (AVF) for patients on hemodialysis (HD). The aim of this study was to compare failure and patency rates of AVF between experienced consultants and resident trainees with special focus on location of the anastomosis on the forearm or upper arm.Between November 2012 and September 2016, 159 patients (83 on HD and 76 preemptive) received an AVF (90 radiocephalic [RCAVF] on the forearm; 69 brachiocephalic [BCAVF] in the elbow) by two experienced vascular surgeons (group A; n = 74) or five residents in training with one-to-four years of experience (group B; n = 85). We compared the two groups for demographic and treatment data, immediate failures (IF), bleeding complications and patency rates.There were no significant differences in demographic data between the two groups. Vessel diameters were significantly lower for forearm compared to upper arm arteries (p = 0.026) and veins (p = 0.05). There was a significantly increased risk for IF in group B for RCAVF (p = 0.003), but not for BCAVF (p = 1.000). Furthermore, the cumulative primary patency was reduced in group B for RCAVF (p<0.001), but not for BCAVF (p = 0.899).Surgeon experience seems to have more influence on the immediate and long-term outcome of newly created forearm AVF compared to those located on the upper arm.
EVALuna2:15320

The Angiosome Concept Evaluated on the Basis of Microperfusion in Critical Limb Ischemia Patients-an Oxygen to See Guided Study - Rother, Ulrich; Kapust, Johannes; Lang, Werner; Horch, Raymund E.; Gefeller, Olaf; Meyer, Alexander (Microcirculation, 2015)
Aim of this clinical study was to evaluate the angiosome concept with regard to the microcirculation of the foot in patients with CLI and to evaluate its relevance by means of combined laser Doppler flowmetrie and white-light tissue spectrophotometry.Twenty-eight patients who underwent leg revascularization in the stage of CLI were prospectively examined. The microperfusion was assessed by light guided spectrophotometry. The measuring points were set according to the angiosome concept into direct and indirect revascularized areas of the foot. Investigations were performed pre and postinterventionally and after 4 and 12 weeks in baseline-position as well as in an elevated position of the leg.Microcirculation parameters (oxygen saturation, blood flow, velocity) of the revascularized leg showed a significant increase in elevation and baseline position compared to the preoperative values in most analyses. No significant differences between the direct and indirect revascularized angiosome were apparent.The light-guided spectrophotometry measurement proved to be feasible in terms of measuring changes in the microcirculation after leg revascularization. However, our data do not support the value of the "angiosome concept" concerning the individual changes in microperfusion of the foot in patients with CLI.
EVALuna2:5490

Timing of first arteriovenous fistula cannulation in children on hemodialysis - Almási-Sperling, Veronika; Galiano, Matthias; Lang, Werner; Rother, Ulrich; Rascher, Wolfgang; Regus, Susanne (Pediatric Nephrology, 2016)
Due to lower complication rates in comparison to central venous catheter (CVC) arteriovenous fistulas (AVFs) are now the preferred hemodialysis access. Recommendations for the first access cannulation range from 6 to 12 weeks, which could lead to temporary or even permanent preference for CVC while awaiting the maturation of the newly created AVF. The aim of this study was to evaluate the influence of first cannulation of AVFs on primary (PP) and secondary (SP) patency rates in children on hemodialysis (HD).This was a retrospective cohort study of 42 pediatric patients with a median age of 14 (range 7-17) years. At the time of surgical AVF creation 21 patients (end-stage renal disease) were still on HD via CVC or peritoneal catheter, while 21 were pre-emptive with initiation of HD expected within a few weeks. All patients received an AVF by the same experienced surgeon between February 1993 and May 2014. Primary failure (PF) was defined as the inability to use the AVF even once due to absent maturation or occlusion within 4 weeks after creation. PP was defined as the interval from time of access placement to any intervention designed to maintain or reestablish patency, to access thrombosis or the time of measurement of patency, while SP was defined as the total lifespan from creation to access abandonment, end of follow-up or loss.Primary failure was observed in six (14.3 %) of 42 AVFs (all radiocephalic fistulas) within the first 10 days after cannulation. Excluding PF, the PP/SP rates at 1, 3, 6, 12, 18 and 24 months were 100/100, 91/99, 86/98, 76/95, 55/85 and 44/77 %, respectively. There was a significant decrease in PP when first cannulation was performed within the first 30 days after creation compared to first cannulation performed after 30 days (p = 0.004). In terms of PP/SP outcome and timing of the first cannulation, there was no significant difference in thee outcome of PP/SP between first cannulation within the first 45 days after creation and that after 45 days (p = 0.091/0.883).The findings suggest that cannulation of AVF within 30 days after surgical creation reduces PP, while SP may be influenced less by time until cannulation. We also found no significant differences in PP after maturing periods of >45 days.
EVALuna2:15275

Treatment of aortic and peripheral prosthetic graft infections with bovine pericardium - Almási-Sperling, Veronika; Heger, Damaris; Meyer, Alexander; Lang, Werner; Rother, Ulrich (Journal of Vascular Surgery, 2019)
Objective: Graft infections are rare but serious complications of vascular operations. The aim of this study was to evaluate the results of in situ reconstruction with bovine pericardium in infected aortic and peripheral vessel fields. Methods: A retrospective cohort study was conducted with a focus on the treatment of infected grafts with bovine pericardium. We retrospectively reviewed 19 consecutive patients with prosthetic graft infections and in situ repair with bovine pericardium. All operations were done between March 2015 and January 2018. No other materials were used. Excision of the infected graft, radical débridement of the infected tissue, and in situ reconstruction with bovine pericardium were applied in all patients. Short-term outcomes including primary patency, freedom of reinfection, mortality, and complication rates were analyzed. Results: Bovine pericardium was used in 19 patients (84% male) with a median age of 70 years (range, 56-84 years) to reconstruct the descending aorta (n = 1), abdominal aorta (n = 5), iliac artery (n = 4), and femoral artery (n = 9). Graft infections were observed in all patients (one thoracic endovascular aneurysm repair, three infrarenal endovascular aneurysm repairs, two open aortic repairs, four iliac-femoral reconstructions, and nine femoral reconstructions including two closure device infections after coronary angiography). Ten patients (53%) had a complication perioperatively and postoperatively. The 30-day mortality was 10.5%; the total mortality rate after 1 year was 32%. There was no reinfection after bovine reconstruction observed in our cohort. Graft occlusions were detected in two cases during follow-up (median, 6 months; range, 1-47 months). Conclusions: Bovine pericardium reconstruction shows a good short-term outcome after aortic or peripheral graft infections. It is associated with good patency, low reinfection rate, and acceptably low early mortality rate. It can be a good therapeutic option in prosthetic graft infections when in situ repair with a prosthetic (even soaked) or autologous vein or homograft is not recommended or is not possible.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Aortic repair; Infection; Pericardium; Vascular graft

Wound closure by means of free flap and arteriovenous loop: Development of flap autonomy in the long-term follow-up - Rother, Ulrich; Müller-Mohnssen, Helena; Lang, Werner; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E.; Regus, Susanne; Meyer, Alexander (International Wound Journal, 2019)
Free flaps in combination with arterial reconstruction by means of arteriovenous loops or bypass have, meanwhile, been established as a therapeutic option in defect reconstruction for areas without recipient vessels. Our aim was to analyse the long-term performance, flap autonomy, and the flap perfusion. Patients receiving this combined reconstruction at a single-centre institution were included. During follow-up examination, the patency of arterial reconstruction was investigated by duplex ultrasound. Flap micro-circulation was assessed by laser Doppler flowmetry and white light tissue spectrometry (O2C) as well as by indocyanine green fluorescence angiography. Twenty-three patients could be clinically followed up. Duplex ultrasound showed, in four cases, arterial pedicle occlusion in spite of vital flap. Comparison of the O2C perfusion parameters between flaps with occluded pedicles and those with intact inflow showed no significant difference (parameters sO2: P =.82; Flow: P =.31). Similar results were obtained by fluorescence angiography; no significant difference could be detected between both groups (parameters Ingress P =.13; Ingressrate P =.54). Combined vascular reconstruction with free tissue transfer is associated with a good long-term outcome and wound closure. Even after flap transplantation to areas with critical tissue perfusion, the flap can develop autonomy and thus survive after pedicle occlusion.
CRIS-Team Scopus Importer:2019-11-19
Keywords: arteriovenous loop; flap autonomy; flap perfusion; indocyanine green; laser Doppler